Effects of Storage Period, Marketing Channels and Season on Internal and External Quality of Commercial Table Eggs Marketed in Riyadh City (Saudi Arabia) - Alshaikhi,AM (2021)
ABSTRACT Very sparse information is available regarding quality of commercial Table eggs marketed in Riyadh city. The objective of the current study was to evaluate egg quality by determining the internal and external traits of commercial Table eggs marketed in different marketing channels during the summer and winter. Commercial eggs (n = 1440) were bought from four different supermarkets and groceries during the winter and summer season 2018- 2019. A total of 30 eggs were collected monthly from each marketing channel in the winter and summer. Then, individually numbered, weighed and randomly broken down into three empirical groups and stored for 0, 7 or 14 days. The outcomes show that seven and fourteen days of storage led to significant decrease in Haugh unit values, yolk index, specific gravity, shell thickness and shell weight per unit of surface area, and increase in yolk color grade, yolk albumin ratio, yolk and albumin pH and air cell depth. Eggs acquired from supermarkets had significantly higher Haugh unit values and yolk index, and lower yolk color grades, shell density and air cell depth, than those bought from groceries. Eggs that were collected in winter season are found to have significantly higher Haugh unit values, yolk index, specific gravity, shell thickness, shell density, shell weight per unit of surface area and yolk color, and lower, yolk albumin ratio, air cell depth, albumin and yolk pH than those acquired in the summer season eggs. This study showed that the storage period, marketing channels and season play a significant role in affecting quality traits of Table eggs, also those procured from supermarkets and in the winter presented better quality than those found in groceries or in the summer, respectively.